CURRENT STATUS OF GRAPHIC TEACHING METHODOLOGY AND WAYS TO IMPROVE IT (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses the current state of teaching graphics and ways to improve it. Based on technological data and written sources, the author explores the specifics of the topic that have clarified the problem based on the available scientific literature.